Population Growth, Immigration and Labour Market Dynamics - Michael Elsby; Jennifer C. Smith; Jonathan Wadsworth (Institute of Labor Economics (IZA), 2021)
This paper examines the role of population flows on labour market dynamics across immigrant and native-born populations in the United Kingdom. Population flows are large, and cyclical, driven first by the maturation of baby boom cohorts in the 1980s, and latterly by immigration in the 2000s. New measures of labour market flows by migrant status uncover both the flow origins of disparities in the levels and cyclicalities of immigrant and native labour market outcomes, as well as their more recent convergence. A novel dynamic accounting framework reveals that population flows have played a nontrivial role in the volatility of labour markets among both the UK-born and, especially, immigrants.
Keywords: E24; J6; 330; immigration; worker flows; labour market dynamics